A randomized controlled trial of the effects of a prudent diet on cardiovascular risk factors, gene expression, and DNA methylation - the Diet and Genetic Intervention (DIGEST) Pilot study. Issue 1 (December 2016) - Zulyniak, Michael; de Souza, Russell; Mente, Andrew; Kandasamy, Sujane; Nundy, Monisha; Desai, Dipika; Raman, Kripa; Hasso, Ranya; Pare, Guillaume; Beyene, Joseph; Anand, Sonia
Abstract Background Risk of cardiovascular disease (CVD) can be increased by single-nucleotide polymorphisms (SNPs) in the 9p21 region of the genome. However, observational studies have shown that the deleterious effect of 9p21 SNPs on CVD might be offset by consuming a diet rich in fresh fruits and vegetables. This association may be driven by diet-influenced modifications in epigenetic and gene expression profiles. In this pilot study, we aimed to:i . test the feasibility of provision of a 'Prudent' and 'Western' diet outside of a specialized clinic, ii . assess the impact of each diet on cardiovascular risk factors. Methods A single centre, parallel two-arm, pilot randomized controlled trial (RCT) with food provision was conducted in a university teaching hospital outpatient clinic (McMaster university, Hamilton, ON, Canada). The aim was to recruit 80 participants, which allowed for a 10 % dropout. The actual study consisted of 84 apparently healthy participants (69 % women, 18 to 77 years) at low cardiovascular risk. Participants were randomly assigned to follow one of two weight-maintaining diets: 'Prudent' or 'Western' for 2-weeks. The Prudent diet provided <7 % of energy as saturated fat, a polyunsaturated: saturated fat ratio of 1.0, and increased fibre, fruits and vegetables. The Western diet was high in processed foods and sugar, with a moderate quantity of fruit and vegetables. All food was provided. Feasibility outcomes included time to recruitment and retention of participants, successful provision of foods, along with adherence to and palatability of the assigned diets. Secondary outcomes were changes in total cholesterol, low density lipoprotein cholesterol (LDL-C), systolic blood pressure (SBP), and diastolic blood pressure (DBP) to obtain variance and estimates of effect sizes to inform the sample size calculation for a definitive trial. Results Recruitment was undertaken over 2 periods spanning 8 months between May-December, 2012. Response rates were high, with 228 screened participants yielding 84 randomized participants. Eight-two of 84 (98 %) of participants completed the intervention. Self-reported adherence to the diets was excellent (>92 % of provided food consumed). The Prudent diet was 48 % more palatable than the Western diet (P  < 0.05). Participants receiving the Prudent diet showed a trend toward reduced systolic (-4 mmHg;P  = 0.10) and diastolic (-3 mmHg;P  = 0.07) blood pressure, and total cholesterol (-0.24 mmol/L;P  = 0.08), compared to individuals receiving the Western diet. Data collection from all randomized participants was completed within 18 months. Conclusions Recruitment, and retention of apparently healthy, normotensive adults into a feeding study for a 2-week duration is feasible outside of specialized dietary clinic, and modest diet-related changes in biomarkers begin to appear after two weeks. Trial registration NCT01658137 (clinicaltrials.gov).